UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK SIKAP SPIRITUAL PESERTA DIDIK MELALUI BUDAYA RELIGI KELAS XI DI SMA NEGERI 1 MALANG - Iud Maisyaroh; Abdul Jalil; Yorita Febry Lismanda (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The purpose of this study is to discuss the efforts of PAI teachers in shaping the spiritual attitudes of students through the religious culture of class XI at SMAN 1 Malang. PAI teachers who guide Moslem students, provided their knowledge, educated their skills and teacher experienced in accordance with Islamic teachings. The PAI teachings it self is to make Islam as way of life. This research used descriptive qualitative research. Data collection was collected in several ways, such as: observation, interviews and documentation. Data analysis was carried out by giving meaning to the data that was successfully collected and drawn conclusions by describing it descriptively. The validity of the data is obtained through data triangulation techniques, analyzed by data reduction techniques, data presentation and drawing conclusions. The results showed that the efforts of school had been going very well. Teachers try to form a spiritual attitude by training students to have an awareness of getting used to worship or religious activities at school, reading the Qur'an and praying in congregation. Teacher's efforts to overcome obstacles by providing religious activities so that spiritual attitude can be formed. Students also have the support from the teachers, parents and their families.